Evaluation Model of Land Use Spatial Equilibrium Based on Regional Collaborative Remote Sensing Observation - Lu Huang (Advances in Multimedia)
In order to improve the evaluation effect of the balance of land use space, this paper uses computer intelligence technology to assist land space observation and provide basic data for land space planning. Moreover, this paper analyzes the existing land space assessment algorithms, identifies the shortcomings of the traditional algorithms, and improves the traditional methods by combining random forest classification and image texture features. In addition, this paper builds a regional collaborative remote sensing observation model based on the improved algorithm. Furthermore, after the system structure is constructed, the system performance is tested by the simulation method, and the system performance is verified by the experimental analysis method. Finally, the validity of the improved algorithm in this paper is also verified by simulation experiments, and the validity of the model in this paper is verified. The research shows that the method proposed in this paper has certain reliability.